2019
DOI: 10.1055/a-0998-8035
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Outcome of Subacute Thyroiditis

Abstract: Background Subacute thyroiditis (SAT) is a rare inflammatory disease that presents diagnostic challenges. The underlying pathophysiology and prediction of outcomes are elusive. We investigated the long-term follow-up of SAT for up to 30 years and determined predictors for later hypothyroidism. Methods SAT outcome data from 127 patients (age: 47.6 ± 11.0 yrs., BMI: 24.7±4.8 kg/m²) were analyzed retrospectively. Patients with pre-existing and known causes of hypothyroidism unrelated to SAT were excluded. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 27 publications
(51 reference statements)
2
38
2
3
Order By: Relevance
“…Several studies have shown that a higher proportion of patients who had SAT were females ( 12 , 13 , 19 ). In this study, the female-to-male ratio was 2.18:1, and 62.9% of them were in the 40–60 age range, which confirms the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that a higher proportion of patients who had SAT were females ( 12 , 13 , 19 ). In this study, the female-to-male ratio was 2.18:1, and 62.9% of them were in the 40–60 age range, which confirms the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have explored the risk factors for recurrence and hypothyroidism in patients with SAT. The risk of recurrence in patients with SAT was human Page 3 of 20 Accepted Manuscript published as EC-21-0212.R2. Accepted for publication: 21-Jul-2021…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latrofa showed that the Anti-Tg epitope pattern in SAT is different from that in Hashimoto's disease and that the anti-Tg release in SAT disease is transient, with no autoimmune significance (10). It has been hypothesized that patients with autoimmune thyroid disease who have anti-TPO positivity may also develop subacute thyroiditis (8,11) Recently published studies have established that the clinical importance of overlapping of SAT and autoimmune thyroid disease is that autoimmunity has been demonstrated to increase the rate of permanent hypothyroidism after SAT (12)(13)(14)(15)(16). Until recently, an increase in the level of TRAb, just like anti-TPO and anti-Tg, was not expected in patients with SAT.…”
Section: Discussionmentioning
confidence: 99%
“…Schließlich entwickelt der Großteil der PatientInnen nach 6-12 Monaten wieder eine normale Schilddrüsenfunktion [13]. Dennoch kann es bei bis zu einem Viertel der Betroffenen zu einer permanenten Hypothyreose kommen, die eine Schilddrüsenhormonsubstitution mit Levothyroxin erfordert [14].…”
Section: Subakute Thyreoiditis (Thyreoiditis De Quervain Granulomatöunclassified